On the way to the Tokyo Summer Olympic Games (2020). Prevention of severe head and neck injuries in judo: it`s time for action - Kamitani, T.; Malliaropoulos, N. G.; Omiya, M.; Otaka, Y.; Inoue, K.; Onidani, N. (British Journal of Sports Medicine, 2017)
Severe head and neck injuries resulting in death or serious sequelae in judo have been recently reported in Japan,1 2 reaffirming the importance of establishing effective measures to reduce such serious injuries. We describe how and in whom the severe head and neck injuries occur in judo and outline the potentially preventive strategies.Judo is a whole-body sport; however, injuries of the knee, shoulder and fingers are common.3 Head and neck injuries are rarer, with incidences of 2.44 and 1.47 cases per 100.000 judokas per year, respectively, but they tend to be more serious.1 According to accident reports submitted to the All Japan Judo Federation`s System, there were 30 cases of head injury and 19 cases of neck injury reported between 2003 and 2010. Young players aged < 20 years accounted for 90% (27/30) of cases of head injury. Many of the victims of these injuries had < 1 year of experience. Head injuries occurred while being thrown in approximately 70% (21/30) of cases during osoto-gari. Osoto-gari is a common leg throw in which judo players sweep their opponent`s leg out while throwing them backwards. The back of the head is impacted in approximately 60% (14/23) of cases, with the most commonly reported head injury being an acute subdural haematoma. In cases of neck injuries, young players aged <20 years account for approximately 58% (11/19); these players were more experienced, with 68% (13/19) having at least 5 years of judo experience. Approximately, 63% (12/19) of judokas are injured while throwing an opponent. The most common technique involved in neck-injured players is uchi-mata, followed by seoi-nage. In uchi-mata, judo players rotate their body and use their leg to kick their opponent`s inner thigh. Neck injuries may occur when judo players dive head first in a flexed neck position while throwing an opponent. In all but one individual, the diagnosis was cervical spinal cord injury. Severe head and neck injury in judo carries a poor prognosis. Of 30 judokas with head injuries, 15 died, 11 had severe sequelae and only four experienced full recovery. Of 19 judokas with head injuries, seven had complete quadriplegia, seven had incomplete paralysis and five experienced full recovery.